(untitled) (AYUSHDHARA, 2019)
In last 10 years significant decrease in human fertility has been observed. Male factor contributes to infertility as much as 51.2% according to WHO study of more than 8500 couples. Shuddha Gandhaka and Kamdeepaka Rasa have Vrishya property expected to contribute better in infertility. Gandhaka Shodhana was prepared as per Rasatarangini and Kamdeepaka Rasa as per Bhaishajya Ratnavali, Vajikarana Adhaya, subjected to Spermatogenic activity on albino rats Method: Kamdeepaka Rasa prepared as per Bhaishajya Ratnavali. Shuddha Gandhaka (9mg), Kamdeepaka Rasa (9mg), milk (0.5ml), male albino rats formed the materials for the study parameter like body weight, biochemical Spermatogenic element, histometric studies and reproductive accessory organ weight were followed. Results: In analytical study Si, S, Zn, were deducted in Gandhaka, Si, S, Cl, K, Ca, Iron, Mg, Zn, and Cu. Kamdeepaka Rasa has shown significant Spermatogenic activity compare to Gandhaka and milk. Conclusion: The chemical and phytochemical component and Balya, Brumhna, Rasayana, and Vrishya properties have contributed for Spermatogenic activity thus Kamdeepakarasa may be used in different condition of Male Infertility.